Errors in air-ground pilot communication: an experimental study - Estival, Dominique; Molesworth, Brett Robert Charles (The ESPecialist, 2020)
Understanding aviation communication has obvious implications for flight safety and for the training of pilots and Air Traffic Controllers (ATCs). Its study also sheds light on the use of Aviation English as a type of English for a very specific purpose and on real-world communication constraints in a high-stakes environment. We present results from a study combining human factors and linguistics, in which pilots were recorded in flight simulator experiments probing communication accuracy under diverse conditions. An analysis of the audio recordings in terms of whether errors were omissions or mistakes, whether errors occurred with words or numerals, and which types of aviation information were affected, revealed complex interactions between language background, pilot qualification, workload and ATC speech rate. The differences between native English speakers (NES) and non-native English speakers (NNES) are complex and more nuanced than might be expected. These results not only are relevant for aviation safety, training and testing, but they also provide insights on communication under challenging conditions and on the relation between language proficiency and cognition, with implications for second language teaching and the use of English for Specific Purposes (ESP) in highly constrained environments.